Two (Postmodern) Czech Shakespearean Adaptations: Claudius and Gertrude and Emodrink of Elsinore - Ivona Mišterová (American and British Studies Annual, 2023)
In her book on adaptation theory, Linda Hutcheon1 argues that “[n]either the product nor the process of adaptation exists in a vacuum: they all have a context - a time and a place, a society, and a culture.” Texts travel from their locus originis to other destinations, times, and contexts, crossing geographical, language, and genre borders, and creating their own palimpsestic identity. As Hutcheon2 states, “an adaptation is a derivation that is not derivative - a work that is second without being secondary.” The objective of the article is to examine two Czech adaptations of Shakespeare’s Hamlet: Claudius and Gertrude (2007) by Jiří Stránský and Jakub Špalek, which was inspired by Saxo Grammaticus and John Updike’s novel Gertrude and Claudius (2000), and Emodrink of Elsinore (2009) by Josef Prokeš. The two plays differ significantly. Stránský and Špalek retell the story that precedes the well-known events at Elsinore and remade the remake. Prokeš, on the other hand, transfers the action to an obscure nightclub, turning Hamlet into a bartender accompanied by a faithful dog (albeit embodied by a human) and incorporating some Czech allusions. The paper focuses on the intertextual aspects of the Czech plays and their vertical rather than horizontal existence.